Analysis of Mathematical Literacy in Solving PISA Problems based on Students' mathematical Ability - Latief Sahidin; Tuti Indah Sari (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to analyze mathematical literacy skills in solving PISA problems in terms of students' abilities. This research is a qualitative research. The research subjects included 3 grade VIII students of SMP Negeri 5 Kendari. Determination of subjects based on the results of the initial test, then grouped and assigned one subject each from the high, medium and low ability groups. Data collection techniques used include initial tests, mathematical literacy tests and interviews. Data analysis includes data reduction, data presentation and conclusion drawing. The results showed that the mathematical literacy skills of high-ability subjects and moderate-ability subjects were able to write down all facts and formulate problems with appropriate verbal descriptions, use appropriate strategies at the completion stage and carry out certain rules or formula calculations and write and verbally describe an illustration. through the relationships of the facts that exist to draw a conclusion correctly. While the subject of low ability, unable to write down the facts completely and not correctly formulating the problem, unable to choose the right strategy to solve problems and carry out calculations both in writing and verbally, and unable to make conclusions.